Re-thinking 3D printing: A novel approach to guided facial contouring. Issue 7 (September 2015) - Darwood, Alastair; Collier, Jonathan; Joshi, Naresh; Grant, William E.; Sauret-Jackson, Veronique; Richards, Robin; Dawood, Andrew; Kirkpatrick, Niall
Abstract Rapid prototyped or three dimensional printed (3D printed) patient specific guides are of great use in many craniofacial and maxillofacial procedures and are extensively described in the literature. These guides are relatively easy to produce and cost effective. However existing designs are limited in that they are unable to be used in procedures requiring the 3D contouring of patient tissues. This paper presents a novel design and approach for the use of three dimensional printing in the production of a patient specific guide capable of fully guiding intraoperative 3D tissue contouring based on a pre-operative plan. We present a case where the technique was used on a patient suffering from an extensive osseous tumour as a result of fibrous dysplasia with encouraging results.